Kakšne uporabniške programske rešitve potrebujemo? - Kovačič, Andrej (Uporabna informatika (Ljubljana), 1997)
Recent studies show that the existing user applications won`t live through the end of the millenium. They will be substituted by object-oriented event/response applications, the type we can already find on the market. These applications support informatization as a modern process-oriented renovation of business. The article provides answers to some of the critical problems that show up whwn we adapt existing applications to the new needs and challenges.
Keywords: informatika; podjetja; poslovna informatika; projekti; računalniški programi